Porous alumina through protein foaming–consolidation method: effect of dispersant concentration on the physical properties - Ahmad, Fadli; Sopyan, Iis; Mel, Maizirwan; Ahmad, Zuraida (Curtin University of Technology and John Wiley & Sons, Ltd., 2011)
The influence of dispersant concentration on the physical properties of porous alumina ceramics formed by the protein foaming–consolidation method has been studied. Slurries of alumina powders, yolk, and dispersant were prepared by rigorously stirring the mixture for 3 h with an alumina-to-yolk ratio of 1 : 1 in weight and dispersantconcentration of 0.01–0.05 wt.%. The resulting slip was poured into cylindrical shaped molds and followed by foamingand consolidation through drying at 180 ◦C for 1 h. The dried green bodies of the samples were then burned to remove the pore-creating agent at 600 ◦C for 1 h, followed by sintering at 1550 ◦C for 2 h. The density of sintered alumina ceramics could be controlled by varying the dispersant concentration of the slurry. Measurement of the average pore size distribution showed that macropores of the sintered alumina porous bodies increased with decreasing density and were found in the range of 54.4 ± 12 to 424.5 ± 25 μm. The compressive strength was 4.6 ± 0.8 MPa at 54.5% porosity and it decreased significantly to 0.8 ± 0.1 MPa at 71.8% porosity. A shrinkage of 29.3 ± 2.7% was observed for the sample prepared using the slurry without dispersant and it increased to 35.8 ± 0.9% when the dispersant of 0.03% was added.